ナンキョク VICTORIA LAND ノ DRY VALLEY チョウサ ホウコク 10 1971 1972ネン ノ VANDAコ ヲ チュウシン ト シタ チキュウ ブツリ オヨビ チキュウ カガクテキ チョウサ ニツイテ ヨホウ ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 鳥居, 鉄也; トリイ, テツヤ; 由佐, 悠紀; ユサ, ユウキ; 中尾, 欣四郎; ナカオ, キンシロウ; 橋本, 丈夫; ハシモト, タケオ; TORII, Tetsuya; YUSA, Yuki; NAKAO, Kinshiro; HASHIMOTO, Takeo (国立極地研究所, 1972)
P(論文) Geophysical and geochemical studies in the Lake Vanda area of the Dry Valleys of South Victoria Land were carried out from the beginning of November, 1971, to the middle of January, 1972, with supplementary studies at Don Juan Pond, Don Quixote Pond, Lake Bonney, and a preliminary survey of the Victoria Valley. The main subjects for study were : pH water and ice temperatures electrical conductivity nutrient matters such as SiO_2-Si, PO_4-P, NH_4-N, NO_2-N, NO_3-N thickness and density of the lake ice ice ablation the melting at the lower surface of the lake ice solar radiation and routine weather observations. departmental bulletin paper